BILIMLENDIRIW PROCESINDE KOGNITIV TEXNOLOGIYALARDÍ PAYDALANÍWDÍŃ ÁHMIYETI - Bekmuratov, Q. (SCIENCE and SOCIETY, 2025)
The article discusses cognitive technologies in education, their role and impact on the educational process. The also provides examples of the use of cognitive technologies, including intelligent teaching systems, mobile applications, educational games, virtual and augmented reality. The advantages and disadvantages of using these technologies are described, as well as their future prospects, such as integration with artificial intelligence and neuroscience.